Effectivity of dolichyl phosphates with different chain lengths as acceptors of nucleotide activated sugars. Issue 7 (July 1986) - Löw, P.; Peterson, E.; Mizuno, M.; Takigawa, T.; Chojnacki, T.; Dallner, G.
Abstract : Chemical synthesis of different S-forms of dolichyl-P was performed in order to investigate the use of these polyprenes in mannosyl, glucosyl and glucosaminyl transferase reactions. Determination of the Vmax values for a series of dolichyl-P demonstrated that the velocities of transferase reactions with all those dolichyl-P derivatives present in animal tissues are largely the same. The apparent K m values for the various dolichyl-P in the transferase system studied differed, but this property does not appear to have physiological importance.